The Role of Counseling Guidance Teachers for Children with Special Needs in Special Schools in Dharmasraya Regency - Alchonity Harika Fitri; Mega Iswari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This research was carried out with the aim of seeing how important counseling and guidance services are in special schools, especially for children with special needs. As well as seeing the main role of counseling guidance teachers to provide counseling guidance services to children with special needs. The main tasks of the guidance and counseling teacher are: organizer, informer, motivator, facilitator, evaluator, mediator, transmitter, initiator, and director. Looking at the task of the counseling guidance teacher, it can be seen that the counseling guidance teacher is able to provide services to students with special needs in special schools. Based on literature studies from journal reviews and articles, it is clear that students with special needs in special schools need counseling guidance teachers to help students face problems in the learning process, student interaction, socialization, as well as in dealing with any obstacles and obstacles faced. Teachers can interact with children with special needs according to different characteristics. Guidance and counseling teachers can act as intermediaries between parents and students with special needs, consulting on matters such as increasing students' motivation to study at home, as well as providing interesting home study tricks and strategies for students with special needs